Analisis Tingkat Kelayakan Bahan Ajar Ekonomi Berbasis Media Komik - Sri Rahayu; Munawaroh Munawaroh; Fahimul Amri (IKIP PGRI Bojonegoro, 2023)
Abstract: Teaching materials are the main problem that cannot be ignored in making teaching materials. Because teachers are expected to be able to create interesting teaching materials as a support for textbooks. To increase students' motivation to read textbooks, teachers must be able to create simple, economical and practical media for students, but effective for the learning process. Comic illustration is a visual medium that can be used in learning to create an active, creative, effective, and fun learning process. Illustration is defined as a picture or form in which there is text. According to this research, the aim is to find out and describe the level of feasibility of comic-based economics teaching materials in the opinion of media experts, comic experts, and economic practitioners, namely economic instructors. Media experts and comic experts cover aspects of simplicity, cohesiveness, emphasis, and balance. In addition, it is reviewed from the aspect of line, shape, space, and color. Meanwhile, economic practitioners cover aspects of learning media, content, language, and appearance. This research uses descriptive research type. Data collection techniques use documents, questionnaires, & observation. The research instrument used was a questionnaire. Data analysis in this study used a qualitative descriptive technique. The results of the study show that the level of feasibility of comic media-based economics teaching materials for senior high schools of class X Social Sciences in odd semester by media experts is an average of 87.83%. The feasibility level of comic-based economics teaching materials by comic experts shows an average of 83.70%. While the feasibility level of economics teaching materials based on comic media by economic practitioners, namely economics teachers, shows an average of 94.67%. Based on the feasibility percentage, it shows that economics teaching materials lined with comic media are very suitable for use in learning. Abstrak: Bahan ajar menjadi persoalan utama yang tidak bisa diabaikan dalam pembuatan bahan ajar. Karena guru diharapkan mampu menciptakan bahan ajar yang menarik sebagai pendukung buku ajar. Untuk meningkatkan motivasi membaca siswa terhadap buku ajar guru harus dapat membuat media sederhana, ekonomis dan praktis bagi siswa, tapi efektif untuk proses pembelajaran. Ilustrasi komik adalah suatu media visual yang dapat digunakan dalam pembelajaran guna menciptakan roses belajar aktif, kreatif, efektif, dan menyenangkan. Ilustrasi diartikan sebagai gambar atau wujud yang didalamnya terdapat teks. Tujuan menurut penelitian ini adalah untuk mengetahui dan menggambarkan taraf kelayakan bahan ajar ekonomi berbasis media komik dipandang menurut ahli media, ahli komik, dan praktisi ekonomi yaitu pengajar ekonomi. Ahli media dan ahli komik meliputi aspek kesederhanaan, keterpaduan, penekanan, dan keseimbangan. Selain itu ditinjau dari aspek garis, bentuk, ruang, dan warna. Sedangkan untuk praktisi ekonomi meliputi aspek media pembelajaran, isi, kebahasaan, dan tampilan. Penelitian ini memakai jenis penelitian deskriptif. Teknik pengumpulan data memakai dokumen, angket, & observasi. Instrument penelitian yang dipakai berupa angket. Analisis data pada penelitian ini memakai teknik deskriptif kualitatif. Hasil penelitian menampakan bahwa tingkat kelayakan bahan ajar ekonomi berbasis media komik bagi Sekolah Menengah Atas kelas X IPS semester ganjil oleh ahli media rata-rata sebesar 87,83%. Tingkat kelayakan bahan ajar ekonomi berbasis media komik oleh ahli komik menunjukkan rata-rata sebesar 83,70%. Sedangkan tingkat kelayakan bahan ajar ekonomi berbasis media komik oleh praktisi ekonomi yaitu guru ekonomi menunjukkan rata-rata sebesar 94,67%. Berdasarkan prosentase kelayakan menunjukkan bahwa bahan ajar ekonomi berbaris media komik sangat layak dipakai dalam pembelajaran.